Analysis Of Patient Service Quality At Kimia Farma Pettarani Clinic - Atira; A. Kartini Sari Putri D (CV Putra Publisher, 2023)
The analysis of the quality of patient service on Chemical Farma Cabang Clinic Pettarani. Thesis study Program Management Faculty of Economics and business of the University of Muhammadiyah Makassar. Guided by Tutors and Mentors Jusriadi Edi I II Muhammad Nur Abdi. The purpose of this research is